A "turn-on" fluorescent sensor for cytosine in aqueous media based on diamino-bridged biphenyl acrylonitrile. (5th January 2021) - Chen, Jiaojiao; Zhou, Bangyi; Li, Yongsheng; Zheng, Linlu; Guo, Hongyu; Yang, Fafu
Abstract : A "turn-on" fluorescent sensor for cytosine in aqueous media was prepared. Abstract : The detection of cytosine is of significance for analyzing DNA bases, but no "turn-on" fluorescent sensor for cytosine in aqueous media has been reported so far. In this study, series of diamino-bridged biphenyl acrylonitriles 3a–3c were designed and synthesized with yields of 70–75%. The sensing experiments for 16 types of ions and biomolecules suggested that compound 3b with butanediamino bridges exhibited good selective sensing abilities towards cytosine based on "turn-on" fluorescence enhancement. The detection limit of compound 3b for cytosine attained 1.02 × 10 −7 M. The selective sensing ability towards cytosine was little influenced by other species and remained stable between pH = 6–9. The sensing mechanism was proposed by the analysis of Job's plot, 1 H NMR and MS binding spectra. The sensing ability for cytosine was successfully used for analysing urine samples with the recovery over 94%. Sample 3b also exhibited good bioimaging performance with bright blue-green fluorescence for sensing cytosine, implying the application prospect in complicated and living environment.